Discovery of EBI-1051: A novel and orally efficacious MEK inhibitor with benzofuran scaffold. Issue 3 (1st February 2018) - Lu, Biao; Huang, Song; Cao, Jingsong; Hu, Qiyue; Shen, Ru; Wan, Hong; Wang, Dan; Yuan, Jijun; Zhang, Lei; Zhang, Jiayin; Zhang, Minsheng; Tao, Weikang; et al.
Graphical abstract: Abstract: A novel series of benzodihydrofuran derivatives was developed as potent MEK inhibitors through scaffold hopping based on known clinical compounds. Further SAR exploration and optimization led to another benzofuran series with good oral bioavailability in rats. One of the compounds EBI-1051 (28d ) demonstrated excellent in vivo efficacy in colo-205 tumor xenograft models in mouse and is suitable for pre-clinical development studies for the treatment of melanoma and MEK associated cancers. Compared to AZD6244, EBI-1051 showed superior potency in some cancer cell lines such as colon-205, A549 and MDA-MB-231.